# Introduction

Now that I have the mathematical definition of substitution, I can implement it. For ease of implementation, I will not consider call by name substitution which requires alpha-conversion. I will implement call by value, which is what most familiar programming languages use, such as Python, Ruby, PHP, C, Perl, and Java to name a few.

# Substitution: Recursive Definition with Alpha Conversion

# Replace all free occurrences of x in x with s
[x ↦ s]x        = s
# Replace all free occurrences of x in y with s
[x ↦ s]y        = y     if x ≠ y
# Replace all free occurrences of x in λy.t1 with s
[x ↦ s](λy.t1)  = λy.[x ↦ s]t1  if y ≠ x and y ∉ FV(s)
# Replace all free occurrences of x in t1 t2 with s
[x ↦ s](t1 t2)  = ([x ↦ s]t1)([x ↦ s]t2)

# Strategy

I basically have four things to consider when substituting in call by value: * If the term is in the form [x ↦ s]x, return the value s * If the term is in the form [x ↦ s]y, return the term y, since x ≠ y * If the term is in the form [x ↦ s](λy.t1), return the substituted abstraction λy.[x ↦ s]t1 * If the term is in the form [x ↦ s](t1 t2), return the application where each term is substituted ([x ↦ s]t1)([x ↦ s]t2)

There are three parts to every substitution: term, variable, and value. So I will need them as parameters to my function; I’ll call them term var value. In mathematical format, you can think of it like this: [var ↦ value]term.

# Implementation in Racket

Using a functional language, like Racket, allows us a more powerful, terse, and elegant solution to the substitution function. I employ the use of Racket’s match which gives extremely powerful pattern matching.

(define (subst term var value)
(match term
; [x -> s]y -> y = x ? s : y
[(? symbol?) (if (eq? term var) value term)]
; [x -> s]λx.b -> λx.b
; [x -> s]λy.b -> λy.[x -> s]b
[(λ (,v) ,body) (if (eq? v var) term (λ (,v) ,(subst body var value)))]
; [x -> s](t1 t2)
[(,f ,a) (,(subst f var value) ,(subst a var value))]))

# Tests

> (subst (λ (x) 'y) 'y '1)
'(λ (x) (1))

> (subst (λ (x) 'y) 'y (λ (x) 'z))
'(λ (x) ((λ (x) 'z)))

> (subst ((λ (x) y) (λ (y) z)) 'z '2)
'((λ (y) 2))

> (subst `((λ (x) y) (λ (y) z)) 'y '2)
'((λ (y) z))